Pemberdayaan Ibu Hamil Dalam Pencegahan Dan Deteksi Dini Terjadi Preeklamsia Pada Ibu Hamil Di Desa Bangun Rejo Tahun 2024 - Nurmalina Hutahaean; Ribur Sinaga; Nova Isabella Napitupu; Elvis Simanjuntak; Rohhasianti Sagala; Merrygrace Simanjuntak (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Preeclampsia is a disease that appears with signs of hypertension, edema, and urine protein that arise due to pregnancy and childbirth. Childbirth with preeclampsia is one of the most critical problems in midwifery care. In Indonesia 30% of maternal deaths are caused by hypertension in pregnancy and in North Sumatra 9 the number of maternal deaths is always dangerously caused by preeclampsia. The aim of this service is to increase and increase knowledge and be able to empower pregnant women in the prevention and early detection of preeclampsia in pregnant women in Bangun Rejo village in 2024.. Results of service to the community shows that the implementation of counseling for pregnant women in improving the quality of life of pregnant women before and after carrying out counseling for pregnant women has obtained significant results in Bangun Rejo village. This can be seen, many pregnant women who have not carried out early detection of preeclampsia have a poor quality of life, as many as 23 people. (76.7%), but after providing counseling to pregnant women, the quality of pregnant women was good, as many as 27 people (90%) in the same group. It is hoped that pregnant women can improve their health by checking themselves from early pregnancy and looking at each examination for signs of preeclampsia and treating it immediately and early detection of preeclampsia can be carried out routinely in Bangun Rejo village once a month by having their pregnancy checked at the Health Facility in 2024.